A cross-sectional study on pain management during vaso-occlusive crisis in sickle cell disease - Jaishetwar, Ganesh S.; Khanam, Fouqia Mahnaz (International Journal of Research in Medical Sciences, 2023)
Background: Sickle cell disease is an inherited hematological disorder characterized by hard and sticky red blood cells that appears like a C-shaped “sickle” in contrast to the healthy, round red blood cells which tend to stick and clog the blood vessels during blood flow leading to pain or vaso-occlusive crisis. Methods: A cross-sectional study was conducted at Yashoda hospital in Hyderabad, India. Data regarding the management of acute pain during VOC in SCD patients was gathered from the hematology department on a daily basis during the duration of the study. The data was recorded in an online questionnaire form and a subsequent DUE was conducted. Results: Among all the patients that were enrolled in the study, acute pain as VOC was presented in 72%, whereas 28% did not experience pain. Pain was manifested as acute chest syndrome, generalized body pain, headache. Crizanlizumab, a monoclonal antibody was administered to patients who were ≥16 years to decrease the frequency of VOC. Upon DUE, per prescription distribution of crizanlizumab was 11.2%, while 88.8% constituted of anti-metabolites, antibiotics, analgesics, opiate antagonist, etc. Frequency of use of crizanlizumab among SCD patients was 69.23% Conclusions: Management of VOC cannot be described as one size fits all. Interindividual variability must be considered at all times during planning and implementing a treatment regimen. Assessment of pain on pain scale to ensure targeted treatment at maximum effective concentration followed by titration of dose to reduce the occurrence of tolerance, withdrawal, dependence and addiction should be basis of management.